The incretin system ABCs in obesity and diabetes – novel therapeutic strategies for weight loss and beyond. (29th April 2016) - João, A. L.; Reis, F.; Fernandes, R.
Summary: Incretins are gastrointestinal‐derived hormones released in response to a meal playing a key role in the regulation of postprandial secretion of insulin ( incretin effect ) and glucagon by the pancreas. Both incretins, glucose‐dependent insulinotropic polypeptide and glucagon‐like peptide‐1 (GLP‐1), have several other actions by peripheral and central mechanisms. GLP‐1 regulates body weight by inhibiting appetite and delaying gastric, emptying actions that are dependent on central nervous system GLP‐1 receptor activation. Several other hormones and gut peptides, including leptin and ghrelin, interact with GLP‐1 to modulate appetite. GLP‐1 is rapidly degraded by the multifunctional enzyme dipeptidyl peptidase‐4 (DPP‐4). DPP‐4 is involved in adipose tissue inflammation, which is associated with insulin resistance and diabetes progression, being a common pathophysiological mechanism in obesity‐related complications. Furthermore, the incretin system appears to provide the basis for understanding the high weight loss efficacy of bariatric surgery, a widely used treatment for obesity, often in association with diabetes. The present review brings together new insights into obesity pathogenesis, integrating GLP‐1 and DPP‐4 in the complex interplay between obesity and inflammation, namely, in diabetic patients. This in turn will provide the basis for novel incretin‐based therapeutic strategies for obesity and diabetes with promising benefits in addition to weight loss. © 2016 World Obesity